Tachlīl al-Khuththah ad-Dirāsiyyah li Māddati ‘Ilmi al-Ashwat fī al-Jāmi’āt al-Indūnīsiyyah fī Dhau`i Kitab “al-Idhā`āt” li ‘Abd ar-Rahmān al-Fauzān - Lubis, Torkis (Al-Arabi: Jurnal Bahasa Arab dan Pengajarannya = Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2023)
In this study, the researcher analyzed the curriculum for the Phonetics course in four Indonesian universities considering the book "Al-Idha'at" by Abdul Rahman Al-Fawzan. Specifically, the study focused on analyzing the course objectives, content, teaching, and learning strategies outlined in the curricula of these four universities. This research is a qualitative desk study with a descriptive-analytical comparative approach. The study found that theoretical or cognitive aspects dominate most teaching objectives for this course. The course content is predominantly theoretical, emphasizing theoretical knowledge over practical skills. Furthermore, most teaching strategies for the course heavily rely on lectures, discussions, questions and answers, and the distribution of assignments, with minimal emphasis on pronunciation exercises for Arabic sounds that are absent in Indonesian phonetics. To address these issues, the researcher suggests complementing the existing strategies in the curriculum with the teaching approach outlined by Abdul Rahman Al-Fawzan in his book "Al-Idha`at," which includes three vocal exercises. قام الباحث في هذه الدراسة بتحليل الخطة الدراسية لمادة علم الأصوات في أربع الجامعات الإندونيسية في ضوء كتاب "الإضاءات" لعبد الرحمن الفوزان، وبالأخص بتحليل الأهداف الدراسية ومحتوى المقررات واستراتيجية التعليم والتعلم المكتوبة في خطط تلك الجامعات الأربع. هذا البحث بحث مكتبي نوعي مع مقاربة وصفي تحليلي مقارن. توصلت الدراسة إلى أن الجانب النظري أو المعرفي يسود جل أهداف تدريس هذه المادة. وأن محتوى مقررات دراسية لهذه المادة يغلب عليها الطابع النظري على حساب الطابع العملي المهارتي. وأن غالبية استراتيجيات لتدريس  المواد المقررة تعتمد كثيرا على المحاضرة والمناقشة والأسئلة والأجوبة وتوزيع الوظيفة الخاصة للمقرر دون اللجوء إلى تدريبات النطق للأصوات العربية المنعدمة في الأصوات الإندونيسية. فلمعالجة هذه المشاكل يقترح الباحث استكمال الاستراتيجيات الموجودة في الخطة باستخدام استراتيجية تعليم مادة علم الأصوات عند عبد الرحمن الفوزان في كتابه "الإضاءات" من خلال التدريبات الصوتية الثلاثة.